Loss of sorting nexin 5 stabilizes internalized growth factor receptors to promote thyroid cancer progression. Issue 3 (17th October 2017) - Jitsukawa, Sumito; Kamekura, Ryuta; Kawata, Koji; Ito, Fumie; Sato, Akinori; Matsumiya, Hiroshi; Nagaya, Tomonori; Yamashita, Keiji; Kubo, Terufumi; Kikuchi, Tomoki; Sato, Noriyuki; Hasegawa, Tadashi; et al.
Abstract: Thyroid carcinoma is the most common endocrine malignancy and its prevalence has recently been increasing worldwide. We previously reported that the level of sorting nexin 5 (Snx5), an endosomal translocator, is preferentially decreased during the progression of well‐differentiated thyroid carcinoma into poorly differentiated carcinoma. To address the functional role of Snx5 in the development and progression of thyroid carcinoma, we established Snx5‐deficient ( Snx5 −/− ) mice. In comparison to wild‐type ( Snx5 +/+ ) mice, Snx5 −/− mice showed enlarged thyroid glands that consisted of thyrocytes with large irregular‐shaped vacuoles. Snx5 −/− thyrocytes exhibited a higher growth potential and higher sensitivity to thyroid‐stimulating hormone (TSH). A high content of early endosomes enriched with TSH receptors was found in Snx5 −/− thyrocytes, suggesting that loss of Snx5 caused retention of the TSH receptor (TSHR) in response to TSH. Similar data were found for internalized EGF in primary thyrocytes. The increased TSH sensitivities in Snx5 −/− thyrocytes were also confirmed by results showing that Snx5 −/− mice steadily developed thyroid tumors with high metastatic potential under high TSH. Furthermore, a thyroid cancer model using carcinogen and an anti‐thyroidal agent revealed that Snx5 −/− mice developed metastasizing thyroid tumors with activation of MAP kinase and AKT pathways, which are postulated to be major pathways of malignant progression of human thyroid carcinoma. Our results suggest that thyrocytes require Snx5 to lessen tumorigenic signaling driven by TSH, which is a major risk factor for thyroid carcinoma. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.